A Clinical Evaluation on the Efficacy of Ayurvedic Intervention in the Management of Hypothyroidism in Women – A Case Study - Manish, Acharya; Richa; Divya; Rani, Tanu; Chandrasekharan, Prabha (International Research Journal of Ayurveda & Yoga, 2026)
In Ayurveda, hypothyroidism is managed by addressing underlying Dosha imbalance, enhancing metabolic fire (Agni), and promoting hormonal regulation through holistic therapeutic interventions. This case study highlights the successful Ayurvedic management of a 35-year-old female patient diagnosed with hypothyroidism, presenting with symptoms such as suppressed TSH levels, generalized body aches, joint pain, dysmenorrhea, irregular menstrual cycles, and leucorrhea. A comprehensive assessment guided an individualized treatment protocol that incorporated Nidan Parivarjan (elimination of causative factors), Shamana Chikitsa (palliative therapy), and lifestyle modifications. Ayurvedic formulations were administered to restore metabolic and hormonal balance. Following the intervention, the patient exhibited remarkable clinical improvement with complete relief of symptoms and normalization of menstrual patterns. The case underscores the efficacy of personalized Ayurvedic management in addressing hypothyroidism holistically, emphasizing its potential to improve endocrine function, metabolic regulation, and overall quality of life in affected women.